Achilles tendons in people with type 2 diabetes show mildly compromised structure: an ultrasound tissue characterisation study. Issue 15 (13th January 2015) - de Jonge, Suzan; Rozenberg, Robert; Vieyra, Bruno; Stam, Henk J; Aanstoot, Henk-Jan; Weinans, Harrie; van Schie, Hans T M; Praet, Stephan F E
Abstract : Background: Musculotendinous overuse injuries are prevalent in people with type 2 diabetes. Non-enzymatic glycosylation of collagen resulting in tendon stiffening may play a role. In this case–control study we determined whether patients with diabetes had poorer ultrasonographic structure in their Achilles tendons compared to age-matched controls. Methods: People with type 1 diabetes or type 2 diabetes, and age-matched controls, had computerised ultrasound tissue characterisation of both Achilles tendons. In contiguous ultrasonographic images of the tendon, echopatterns were quantified and categorised into four echo-types. Tendon abnormality was quantified as sum of echo-types III+IV. Furthermore, skin autofluorescence (AF) of the forearm (AF-value) was gathered. Results: Twenty four type 2 diabetes patients, 24 controls, 24 type 1 diabetes patients and 20 controls were included. AF-value was higher in type 1 diabetes (1.55±0.17) than in their controls (1.39±0.18, p<0.001) and in type 2 diabetes (2.28±0.38) compared to their controls (1.84±0.32, p<0.001) Achilles tendons of type 2 diabetes patients contained more echo-types III+IV (14.1±7.9%) than matched controls (8.0±5.4%, p<0.001). There was a trend towards a difference in echo-types III+IV between type 1 diabetes patients (9.5±5.3%) and their controls (6.5±3.7%, p=0.055). In a stepwise linear regression analysis, body mass index (BMI) was moderately associated with tendon abnormality in patients with diabetes and controls (β=0.393, p<0.001). Conclusions: Type 2, and possibly type 1, diabetes patients showed poorer ultrasonographic Achilles tendon structure that may be a risk factor for tendinopathy. Although markers for accumulation of advanced glycation end products were elevated in both diabetes populations, only BMI was associated with these abnormalities. Trial registration number: NTR2209.